2023
DOI: 10.31219/osf.io/rphs9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disruption to left inferior frontal cortex modulates semantic prediction effects in reading and subsequent memory: Evidence from simultaneous TMS-EEG

Abstract: Readers use prior context to predict features of upcoming words. When predictions are accurate, this increases the efficiency of comprehension. However, little is known about the fate of predictable and unpredictable words in memory or the neural systems governing these processes. Several theories suggest that the speech production system, including the left inferior frontal cortex (LIFC), is recruited for prediction but evidence that LIFC plays a causal role is lacking. We first examined the effects of predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 102 publications
1
2
0
Order By: Relevance
“…We found that high-constraint sentences were generally remembered better than low-constraint sentences and that expected sentence-final words were recalled better than unexpected sentence-final words. In general, this adds to the growing literature that engaging in predictive processes can benefit memory (e.g., Silcox, Mickey, & Payne, 2023;Silcox & Payne, 2021;Gordon-Salant & Fitzgibbons, 1997;Kutas, 1993). The results from the current study also showed that prediction is not just helpful when a prediction turns out to be correct but also when it is incorrect.…”
Section: The Impact Of Acoustic Challenge On Memorysupporting
confidence: 73%
See 2 more Smart Citations
“…We found that high-constraint sentences were generally remembered better than low-constraint sentences and that expected sentence-final words were recalled better than unexpected sentence-final words. In general, this adds to the growing literature that engaging in predictive processes can benefit memory (e.g., Silcox, Mickey, & Payne, 2023;Silcox & Payne, 2021;Gordon-Salant & Fitzgibbons, 1997;Kutas, 1993). The results from the current study also showed that prediction is not just helpful when a prediction turns out to be correct but also when it is incorrect.…”
Section: The Impact Of Acoustic Challenge On Memorysupporting
confidence: 73%
“…Indeed, over the last 70 years (Black, 1952;Howes & Osgood, 1954;Miller, 1951;Taylor, 1953), studies have explored the effects of prior linguistic context on perception and comprehension and have reliably shown that words congruent with (and more predictable from) prior context are facilitated in processing relative to less expected input. Predictable words show faster visual and auditory word recognition in lexical decision tasks (Schwanenflugel & Shoben, 1985;Fischler and Bloom, 1979), shorter fixation durations during natural reading (Staub, 2015), improved word recognition in noise (Pichora-Fuller et al, 1995), improved memory (Gordon-Salant & Fitzgibbons, 1997;Kutas, 1993;Silcox, Mickey, & Payne, 2023;Silcox & Payne, 2021), and facilitated semantic processing as revealed by recordings of event-related brain potentials (ERPs) (Kutas & Federmeier, 2011;Federmeier, 2022).…”
Section: Context Use and Agingmentioning
confidence: 99%
See 1 more Smart Citation